Implementasi Sertifikasi dan Pendidikan Profesi Guru Masa Kini di UPT SD Negeri 13 Bontolebang - Ati, Andi; R, Rosdiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the implementation of the teacher certification and Teacher Professional Education (PPG) programs and their impact on improving teacher competence at UPT SD Negeri 13 Bontolebang, Takalar Regency. This research used a qualitative approach with descriptive methods. Data collection techniques included in-depth interviews, observation, and documentation. The informants in this study were teachers who had participated in certification and PPG, the school principal, and the supervising officer. Data were analyzed using data reduction, data display, verification, and validity testing through source triangulation, technique triangulation, and time triangulation. The results showed that the implementation of certification and PPG programs at UPT SD Negeri 13 Bontolebang has proceeded fairly well, although there are still obstacles related to limited technological facilities, lack of follow-up training, and incomplete access to policy information. Teachers who completed the programs demonstrated improvements in lesson planning, content mastery, and active learning strategies. The implementation of this research highlights that certification and PPG contribute significantly to strengthening teachers’ professional competence and fostering more effective and quality-oriented learning processes. These findings can serve as a reference for education offices and schools to design more contextual and targeted professional development programs.